2022
DOI: 10.1038/s43247-022-00638-9
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions from agricultural ponds are underestimated in national greenhouse gas inventories

Abstract: Agricultural ponds have some of the highest methane emissions per area among freshwater systems, and these anthropogenic emissions should be included in national greenhouse gas inventories. Here we deliver a continental-scale assessment of methane emissions from agricultural ponds in the United States and Australia. We source maps of agricultural ponds, compile a meta-analysis for their emissions and use published data to correct for temperature and the relative contributions of two methane fluxes (diffusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Our unique whole-ecosystem experiment demonstrated that eutrophication arising from N fertilizer amendments did not induce large increases in diffusive summer GHG emissions from small farm reservoirs (Figure g) representative of Canada’s largest agricultural region. , These findings sharply contrast expectations based on lake and pond surveys. ,,, As expected based on small-scale controlled experiments, fertilization enhanced reservoir productivity (as chl a, Figure d) and uptake of atmospheric CO 2 (Figure ). Yet, unexpectedly, this effect was offset by marginally increased N 2 O fluxes, combined with a limited response of CH 4 (Figure ), resulting in no net effect on total emissions as CO 2 -eq from these ecosystems (Figure g).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our unique whole-ecosystem experiment demonstrated that eutrophication arising from N fertilizer amendments did not induce large increases in diffusive summer GHG emissions from small farm reservoirs (Figure g) representative of Canada’s largest agricultural region. , These findings sharply contrast expectations based on lake and pond surveys. ,,, As expected based on small-scale controlled experiments, fertilization enhanced reservoir productivity (as chl a, Figure d) and uptake of atmospheric CO 2 (Figure ). Yet, unexpectedly, this effect was offset by marginally increased N 2 O fluxes, combined with a limited response of CH 4 (Figure ), resulting in no net effect on total emissions as CO 2 -eq from these ecosystems (Figure g).…”
Section: Discussionmentioning
confidence: 95%
“…28,29 These findings sharply contrast expectations based on lake and pond surveys. 5,6,42,43 As expected based on small-scale controlled experiments, 8 fertilization enhanced reservoir productivity (as chl a, Figure 1d) and uptake of atmospheric CO 2 (Figure 2). Yet, unexpectedly, this effect was offset by marginally increased N 2 O fluxes, combined with a limited response of CH 4 (Figure 2), resulting in no net effect on total emissions as CO 2 -eq from these ecosystems (Figure 2g).…”
Section: Eutrophication Causes Contrasting Effects On Ghgsmentioning
confidence: 94%
“…Although carbon dioxide (CO 2 ) is a major contributor, CH 4 is ~84 times more potent than CO 2 as a key greenhouse gas. [1][2][3] Driven by agriculture and industries using natural gas, global CH 4 emission have continued to increase over the past two decades. From 2000-2017, the annual emission of CH 4 has increased by approximately 50 million tonnes, reaching a record high of around 600 million tonnes in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Global warming is one of the most challenging and urgent global problems. Although carbon dioxide (CO 2 ) is a major contributor, CH 4 is ~84 times more potent than CO 2 as a key greenhouse gas [1–3] . Driven by agriculture and industries using natural gas, global CH 4 emission have continued to increase over the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Constructed ponds are already prominent landscape features (e.g., 25% of all runoff in the coterminous United States is captured by a constructed pond; Renwick et al., 2006) and are likely to play an important role in both current and future global GHG and C cycling. For instance, the global number of constructed ponds is increasing as new ponds are built to provide climate‐resilience in agricultural systems, manage stormwater in urban areas, provide food through inland aquaculture production, and for leisure activities (FAO, 2020; Malerba et al., 2022; Sinclair et al., 2020). Yet, GHG emission estimates from ponds at a global scale are still highly uncertain (Canadell et al., 2021; Rosentreter et al., 2021).…”
Section: Introductionmentioning
confidence: 99%